Advances in quantum electronics. - Goodwin, D. W. (Academic Press, 1975)
Advances in Quantum Electronics, Volume 3 covers articles on the theoretical and experimental work undertaken in the field of optical pumping and on gaseous ion lasers. The book presents an overview of the optical-pumping field and a review of the use and properties of the density matrix as applied to the statistical behavior of assemblages of atoms or ions. The text discusses the application of the density matrix approach to the theory of optical-pumping r.f. spectroscopy and spin-exchange optical pumping. Optical-pumping experiments are also considered. The book further provides a comprehens.